2022
DOI: 10.1021/acsomega.2c05973
|View full text |Cite
|
Sign up to set email alerts
|

Local Electric Field and Electrical Conductivity Analysis Using a Glass Microelectrode

Abstract: Transport phenomena in microfluidic chips are induced by electric fields and electrolyte concentrations. Liquid flows are often affected by ionic currents driven by electric fields in narrow channels, which are applied in microelectromechanical systems, microreactors, lab-on-a-chip, and so forth. Even though numerical studies to evaluate those local fields have been reported, measurement methods seem to be under construction. To deeply understand the dynamics of ions at the microscale, measurement techniques a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The glass tip size may be shrunk with nanoporous structures of the agent, which is expected to increase the ion selectivity. In a previous study, we demonstrated the effectiveness of agarose gel fixed in the glass tip . On the other hand, agars usually form gels when heated, and they have to be quickly brought to the tip of a narrow glass capillary before they harden.…”
Section: Experimental Methodsmentioning
confidence: 96%
See 2 more Smart Citations
“…The glass tip size may be shrunk with nanoporous structures of the agent, which is expected to increase the ion selectivity. In a previous study, we demonstrated the effectiveness of agarose gel fixed in the glass tip . On the other hand, agars usually form gels when heated, and they have to be quickly brought to the tip of a narrow glass capillary before they harden.…”
Section: Experimental Methodsmentioning
confidence: 96%
“…In a previous study, we demonstrated the effectiveness of agarose gel fixed in the glass tip. 38 On the other hand, agars usually form gels when heated, and they have to be quickly brought to the tip of a narrow glass capillary before they harden. It is difficult to put the warmed gel into the tip by tapping the glass tube.…”
Section: Electrical Measurement Setup As Shown In Figurementioning
confidence: 99%
See 1 more Smart Citation